PERAN KECERDASAN BUATAN DALAM DUNIA PENDIDIKAN DI ERA ARTIVICIAL INTELLEGENCI ( AI ) PADA SDN INPRES DOYO LAMA - Dike, Yosina; Satyawati, Sophia Tri; Wasitohadi, Wasitohadi (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
This research aims to identify the challenges and opportunities in implementing artificial intelligence (AI) at SDN Inpres Doyo Lama. Through a qualitative approach, this study involved in-depth interviews with teachers, students, and the school principal. The results showed that the main constraints in implementing AI were the lack of adequate infrastructure, as well as the limited knowledge and skills of teachers in utilizing AI technology. However, this study also identified the great potential of AI in improving the quality of education, especially in terms of personalized learning and access to a wider range of learning materials.